2016
DOI: 10.1016/j.exer.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid action in human corneal epithelial cells establishes roles for corticosteroids in wound healing and barrier function of the eye

Abstract: Glucocorticoids play diverse roles in almost all physiological systems of the body, including both anti-inflammatory and immunosuppressive roles. Synthetic glucocorticoids are one of the most widely prescribed drugs and are used in the treatment of conditions such as autoimmune diseases, allergies, ocular disorders and certain types of cancers. In the interest of investigating glucocorticoid actions in the cornea of the eye, we established that multiple cell types in mouse corneas express functional glucocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 42 publications
6
26
0
1
Order By: Relevance
“…The present study demonstrated that prolonged stress exposure resulted in significantly increased serum glucocorticoid levels, suggesting an increased defense capability to external stimuli by regulating the HPA axis and ultimately maintaining homeostasis. Numerous studies have indicated that glucocorticoids play a critical role in maintaining cardiovascular stability, stabilizing lysosomal membranes, anti-inflammation, anti-shock mechanisms, and reducing bacterial endotoxin damage (Kasahara et al, 2015; Kadmiel et al, 2016). However, by increasing the stress period to 21 days, serum glucocorticoid levels significantly decreased compared with stress exposure of 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that prolonged stress exposure resulted in significantly increased serum glucocorticoid levels, suggesting an increased defense capability to external stimuli by regulating the HPA axis and ultimately maintaining homeostasis. Numerous studies have indicated that glucocorticoids play a critical role in maintaining cardiovascular stability, stabilizing lysosomal membranes, anti-inflammation, anti-shock mechanisms, and reducing bacterial endotoxin damage (Kasahara et al, 2015; Kadmiel et al, 2016). However, by increasing the stress period to 21 days, serum glucocorticoid levels significantly decreased compared with stress exposure of 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…As such, glucocorticoid receptor (GR), a stress transcription factor, has shown to play a role in RPE physiology and AMD progression. Activation of GR by Dex-induced proliferation of cultured retinal pigment epithelial cells [33] and loss of GR in the retina result in the thinning of the inner nuclear layer of the peripheral retina in adult mice [34]. Because AHR and GR are closely related in AMD progression, we attempted to study AHR and GR crosstalk in ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…; Kadmiel et al. ). Fluorometholone is a fluorinated corticosteroid that has been shown to be efficacious in relieving the symptoms of dry eye in non‐Sjogren and Sjogren's patients (Jee et al.…”
Section: Introductionmentioning
confidence: 98%